Political economy of central-bank mandates in developing countries - Zhandos Ybrayev (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
In this paper, I explain theoretically the coordination and conflict scheme of fiscal and monetary policy workings, and then empirically assess the effect of both inflation-targeting and non-inflation-only targeting policies on inflation and unemployment rates. I employ a difference-in-difference method to estimate the impact on inflation, the unemployment rate, and their volatilities in both 10 inflation-targeting (single-mandate) and 11 non-inflation-targeting (multiple-mandate) countries specifically from the sample of developing economies over the period from 1998 to 2018. Our key findings show that while the inflation-targeting countries effectively present a reduction in inflation and inflation volatility, the effects on the unemployment rate are negligible, while unemployment volatility is higher in the period 1998–2008. Finally, the paper argues that the unemployment rate should be used as a natural second target in a typical emerging-market economy case.
Keywords: 330; inflation targeting; central banking; unemployment; political economyE52; E58; E61; E63